Trade union solidarity in an export-oriented sector - some experiences from the Polish automotive industry - Sławomir Adamczyk; Barbara Surdykowska (Italian Labour Law e-Journal, 2025)
This paper explores the challenges and limitations of trade union solidarity in Poland's automotive sector, a key export-oriented industry dominated by multinational corporations. Drawing on an analysis of the sector's structure and industrial relations, as well as selected case studies of company-level trade union practices, the authors examine the feasibility of introducing collective bargaining at a sector level in Poland. The paper highlights how organisational structures inherited from the past, employer strategies and national industrial policy all contribute to the weakness of higher-level union coordination. Despite some workplaces having a high level of unionisation, union activity remains fragmented and is embedded in corporate logics. This undermines the potential for coordinated action in response to the dual transition (green and digital) and growing global competition. The authors argue that, without systemic changes and state incentives to promote sectoral bargaining, the Polish automotive workforce risks becoming further marginalised in restructuring processes driven by external pressures.